Comparison of haematological indices and transfusion management in severe and massive postpartum haemorrhage: analysis of a two-year national prospective observational study. (May 2022) - Bell, S.F.; Collis, R.E.; Collins, P.W.
Highlights: A prospective cohort study compared severe and massive postpartum haemorrhage (PPH). Red blood cells were transfused to 42.5% severe and 80.6% massive PPH cases. Hypofibrinogenemia occurred in 5.4% severe and 17.0% massive PPH cases. Blood coagulation products were received by 3.6% severe and 22.9% massive PPH cases. Early targeted fibrinogen therapy in cases of abruption requires further evaluation. Abstract: Introduction: This two-year prospective cohort study compared the management of women experiencing severe or massive postpartum haemorrhage (PPH) to explore the impact of targeted blood product administration on reducing PPH progression (from >1500 mL to ≥2500 mL blood loss). During the study, viscoelastic haemostatic assays (VHA) guided blood product transfusion. Methods: All women experiencing blood loss after PPH >1000 mL were included in a national database. Haematological indices, transfusion and PPH aetiology were analysed in severe (>1500 mL blood loss or transfusion of any blood product) and massive PPH (≥2500 mL blood loss or transfusion ≥5 units red blood cells) . Results: Of the 61 094 maternities in Wales (2017 to 2018), 2111 had severe and 349 massive PPH. Red blood cells were transfused to 42.5% severe and 80.6% massive PPH cases. Hypofibrinogenaemia (fibrinogen <2 g/L and/or Fibtem A5 <12 mm) was the most frequent coagulation abnormality, occurring in 5.4% severe and 17.0% massive PPH, with blood coagulation products (fresh frozen plasma, platelets, cryoprecipitate and/or fibrinogen concentrate) administered to 3.6% and 22.9%. Women with hypofibrinogenaemia received targeted fibrinogen replacement in 97.8% severe and 93.6% massive PPH. The only aetiology with similar rates of hypofibrinogenaemia in severe and massive PPH was abruption (40.0% and 36.8%). Conclusion: Hypofibrinogenaemia was less frequent in severe PPH, although coagulopathy was observed across a range of PPH aetiologies, highlighting the importance of coagulation testing for all. Cases of abruption in severe and massive PPH had similar rates of hypofibrinogenaemia. Early VHA-guided fibrinogen replacement may reduce PPH progression in abruption and requires further evaluation.